FORMULATION OF SOLID BATH SOAP PREPARATIONS OF PURPLE SWEET POTATO ETHANOL EXTRACT (IPOMEA BATATAS L) AS A SKIN MOISTURIZER - Wulandari, Suci; Niasari Silaen, Ayu Renta; Wahyuni, Siti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Soap is a surfatctant used to clean or wash something that is available in solid and liquid form. Soap can be useful as a cleaning tool, this is because soap molecules contain polar (bonded with water) and non-polar (bonded with oil) groups so that they can clean grease or dirt that is not lifted by water. Soap is made by applying a saphonification reaction using olive oil, NaOH, and purple sweet potato extract as the basic ingredients. The addition of NaOH concentration an affect the weight of the soap produced. Purple sweet potato is a sweet potato that has natural dyes a anthocyanins that function as antioxidant. The purpose of this study was to obtain a solid bath soap formulation with purple sweet potato extract. Furthermore, purple sweet potato extract was formulated based on formula with concentration difference of 3,5%, 4,5%, 5,5%. Furthermore, preparations have been made with organoleptic tests, pH tests, and foam stability tests. It can be concluded that purple sweet potato extract can be used as a solid soap preparation and there is a concentration effect on the organoleptic test soap quality, pH, foam stability and moisture content. The preparation of solid bath soap from purple sweet potato ethanol extract has the ability to moisturize the skin, and the highest concentration obtained at a concentration of 5,5% with 57,83% moisture can moisturize the skin and at concentration of 4,5% with 48,3% humidity as well. Can moisturize the skin but with a moderate level of humidity, and at a concentration of 3,3% with 43,00% humidity with a lower humidity level.